Framework for performance assessment of wind farms - Vaz, Clara B. (2014)
This study develops a framework to provide insights regarding the performance of the farms of an energy player in the Portuguese wind sector. Firstly, the Data Envelopment Analysis is used to measure the efficiency of wind farms in producing electrical energy from the resources available and exogenous variables, during operating stage. This analysis enables the identification of the best practices of the efficient farms which can be emulated by inefficient ones. Secondly, Malmquist index is used to evaluate the changes in wind farms productivity. Bootstrap procedures are applied to obtain statistical inference on the efficiency estimates.